2020
DOI: 10.1016/j.ajoc.2020.100884
|View full text |Cite
|
Sign up to set email alerts
|

There is no intraocular affection on a SARS-CoV-2 - Infected ocular surface

Abstract: Purpose The presence of SARS-CoV-2 RNA in anterior chamber fluid and/or the vitreous in patients with SARS-CoV-2 RNA on the ocular surface is unclear. Knowledge about the infectious state of intraocular structures could influence the daily work of ophthalmic surgeons. Observations We analyzed ocular samples from a patient who had succumbed to COVID-19 pneumonia for the prevalence of SARS-CoV-2 RNA. We detected viral RNA in the ocular-surface samples on one swab and in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 6 publications
0
11
0
2
Order By: Relevance
“…There is also evidence of SARS-CoV-2 RNA detection in the retinal biopsies of COVID-19 patients [19]. However, the results of a case report revealed no definitive SARS-CoV-2 RNA from the vitreous samples [20]. Besides the ACE receptor, CD147, a transmembrane glycoprotein, has been shown as another possible receptor for binding to the host cells [21].…”
Section: Discussionmentioning
confidence: 99%
“…There is also evidence of SARS-CoV-2 RNA detection in the retinal biopsies of COVID-19 patients [19]. However, the results of a case report revealed no definitive SARS-CoV-2 RNA from the vitreous samples [20]. Besides the ACE receptor, CD147, a transmembrane glycoprotein, has been shown as another possible receptor for binding to the host cells [21].…”
Section: Discussionmentioning
confidence: 99%
“…None of the patient had any ocular manifestation in our study. SARS-CoV-2 wasn't detected in study done by List W et al [17] (16 cases), Lauermann P et al [18] (1 case) and Bayyoud T et al [19] (1 case). Recent studies have found SARS-CoV-2 in tear and conjuctival swabs in even in patients who hadn't any ocular manifestation.…”
Section: Resultsmentioning
confidence: 92%
“…Very few studies have focused on detection of SARS-CoV-2 in vitreous humor, CSF, pleural uid and pericardial uid. [17][18][19][20][21][22][23][24][25][26][27][28][29][30] Number of cases were also less in most such studies. In our study, we have collected postmortem samples of vitreous humor, CSF, pleural uid and pericardial uid in 24 cases and analyzed them to detect SARS-CoV-2 by RT-PCR.…”
Section: Introductionmentioning
confidence: 99%
“… 25 Recent evidence demonstrated the presence of SARS-CoV-2 in the vitreous and cornea, highlighting the criticality of donor screening guidelines and the plausibility of human eye tissue or eye fluids to be a source of infection. 24 , 26 …”
Section: Covid-19 Pandemicmentioning
confidence: 99%
“…25 Recent evidence demonstrated the presence of SARS-CoV-2 in the vitreous and cornea, highlighting the criticality of donor screening guidelines and the plausibility of human eye tissue or eye fluids to be a source of infection. 24,26 The ocular manifestations of COVID-19 include mainly signs and symptoms compatible with follicular conjunctivitis. The incidence of conjunctivitis is estimated around 1% to 3% and is related in a meta-analysis to more severe forms of COVID-19.…”
Section: Sars-cov-2 and Eyementioning
confidence: 99%